Characteristics and factors influencing hypothalamic pituitary dysfunction in patients with craniopharyngioma - Guo, Ying; Pei, Lili; Li, Yuzheng; Li, Chunde; Gui, Songbai; Ni, Ming; Liu, Pinan; Zhang, Yazhuo; Zhong, Liyong (Frontiers in Endocrinology, 2023)
Background: Craniopharyngioma is a benign tumor originating from the sellar region. Damages in this area caused by the tumor itself, surgery, or radiotherapy may result in severe hypothalamic-pituitary dysfunction (HPD) and eventually lead to a significant impairment in the long-term quality of life of patients. This study aimed to investigate the characteristics of HPD in patients with adamantinomatous craniopharyngioma (ACP) or papillary craniopharyngioma (PCP) and to identify the factors affecting HPD after surgery. Methods: In this single-center retrospective study, a total of 742 patients with craniopharyngioma were included. The neuroendocrine function of these patients before and after surgery was investigated. The differences in hypothalamic-pituitary function between the ACP and PCP groups were compared. The factors influencing the aggravation of HPD after surgery were identified. Results: The median follow-up after surgery was 15 months. Before surgery, the proportion of patients with diabetes insipidus (DI) and hyperprolactinemia in the PCP group was significantly higher than that in the ACP group (P<0.01), and the proportion of patients with adrenocortical hypofunction in the PCP group was significantly lower than that in the ACP group (P=0.03). Most cases of ACP originated in the sellar region, while most cases of PCP originated in the suprasellar region (P<0.01). More patients experienced adenohypophyseal hypofunction, DI, and hypothalamic obesity at postoperative follow-up than at onset in both the ACP and PCP groups (both P<0.01), with a higher increase observed in the ACP group (P<0.01). Older age at CP onset, tumor recurrence or progression, and ACP type were risk factors for postoperative aggravation of HPD in CP patients. Conclusion: Surgical treatment significantly aggravated HPD in both the ACP and PCP groups, but the specific characteristics and risk factors leading to aggravation were different between the two groups.